BUDIDAYA KEPITING BAKAU (Scylla sp.) DI WILAYAH PESISIR KECAMATAN MA’RANG KABUPATEN PANGKEP SULAWESI SELATAN - Muhammad Ikhsan Wamnebo; Abdul Rauf (Buletin SWIMP, 2021)
Ma'rang sub-district is one of the sub-districts in Pangkajene Islands Regency. This area has mangrove forests that spread along the coast where there are many potential fishery resources, one of which is the mangrove crab (Scylla sp). The people of Ma'rang Subdistrict, especially in the coastal area of Tamangapa Village, generally have professions as fishermen and pond and seaweed farmers who depend on the results of these activities and have recently experienced a decline in production so that they require alternative activities to support the activities that have been carried out so far. one of them is using mangroves for the cultivation of mud crab (Scylla sp). So far, coastal communities in this area have only caught it so that it has the potential to threaten the survival of the mangrove crab (Scylla sp). The purpose of this service is to help facilitate coastal community groups in Ma'rang District through training in the cultivation of mangrove crabs (Scylla sp), so that they can carry out mangrove crab cultivation on an ongoing basis. The method used in the training is a participatory training method, which involves as many partners as possible in the activities of lectures, discussions, and the practice of design and creation of works. The program that has been agreed with business group partners is carried out using the training method for mud crab (Scylla sp) cultivation. The results achieved from the implementation of this service are an increase in the understanding, knowledge and skills of group partners on how to cultivate mud crabs with silvofishery patterns..